Pentingnya Peranan Guru Kristen dalam Membentuk Karakter Siswa Dalam Pendidikan Kristen: Sebuah Kajian Etika Kristen [The Significance of the Role of Christian Teachers in Building Students’ Character in Christian Education: A Study of Christian Ethics] - Kiki Debora; Chandra Han (Diligentia: Journal of Theology and Christian Education, 2020)
Transformation for the nation's generation can be done through education because education has a very important influence on the nation's generation. Christian education is not only talking about ways to educate children of the nation, but also Christian education is holistically paying attention to the entire existence of students. The development of the modern era has caused the character of the nation's generation to decline and moral damage is getting higher. The role of the qualified Christian teachers is very important in improving the quality of education, especially students. Beside the parents, teachers have a big influence in the life the of students. The Christian education is not just to improve science, but to shape the character of students through the role of Christian teachers who have experienced a new birth because only Christian teachers who have been born again are able to do good deeds because the Holy Spirit enables them. Every example of good deeds done by a Christian teacher will influence the formation of student character. Christian teachers who have experienced a new birth as agents of transformation took change play a role in shaping the character of students. The formation of student character aims to make students know the truth and errors and the meaning of each action they do. Through correct understanding students are able to make decisions and take responsibility in the modern era. The purpose of this paper is to demonstrate the important role of Christian teachers in shaping students' character through Christian education. This paper begin with some explanations of the study focus based on the title. The next explanation is to examine the role of the Christian teacher in shaping students’ character and finally make conclusions and suggestions.